Jordan Permuting 3-Derivations of Prime Rings - Faraj , Anwar K.; Shareef , Sabreen J. (Iraqi Journal of Science, 2022)
The main purpose of this work is to generalize Daif's result by introduceing the concept of Jordan (α β permuting 3-derivation on Lie ideal and generalize these result by introducing the concept of generalized Jordan (α β permuting 3-derivation